Tetrazine as a general phototrigger to turn on fluorophores. Issue 17 (17th April 2020) - Loredo, Axel; Tang, Juan; Wang, Lushun; Wu, Kuan-Lin; Peng, Zane; Xiao, Han
Abstract : Tetrazine was demonstrated for the first time as a general phototrigger to design photoactivatable fluorophore probes. Abstract : Light-activated fluorescence affords a powerful tool for monitoring subcellular structures and dynamics with enhanced temporal and spatial control of the fluorescence signal. Here, we demonstrate a general and straightforward strategy for using a tetrazine phototrigger to design photoactivatable fluorophores that emit across the visible spectrum. Tetrazine is known to efficiently quench the fluorescence of various fluorophores via a mechanism referred to as through-bond energy transfer. Upon light irradiation, restricted tetrazine moieties undergo a photolysis reaction that generates two nitriles and molecular nitrogen, thus restoring the fluorescence of fluorophores. Significantly, we find that this strategy can be successfully translated and generalized to a wide range of fluorophore scaffolds. Based on these results, we have used this mechanism to design photoactivatable fluorophores targeting cellular organelles and proteins. Compared to widely used phototriggers ( e.g., o -nitrobenzyl and nitrophenethyl groups), this study affords a new photoactivation mechanism, in which the quencher is photodecomposed to restore the fluorescence upon light irradiation. Because of the exclusive use of tetrazine as a photoquencher in the design of fluorogenic probes, we anticipate that our current study will significantly facilitate the development of novel photoactivatable fluorophores.